Correlation of range of motion and functional performance of upper extremities in children with cerebral palsy - Suwimol Prusmetikul (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: Upper extremity deformities in children with cerebral palsy greatly affects their functioning and their daily activities. Range of motion of the upper extremity joints in children with cerebral palsy is usually limited. There is little information available, however, regarding the relation between range of motion and functional outcomes of upper extremities in children with cerebral palsy. The purpose of this study was to determine the correlation both between the Upper Extremity Rating Scale [UERS] and the Manual Ability Classification System [MACS] and also between the UERS test and the Box and Block Test [BBT]. Materials and Methods: Fifty-seven children with cerebral palsy were enrolled in this cross-sectional study. Their range of motion was rated using the UERS, their ability to handle objects in daily activities was evaluated using MACS, and manual dexterity ofthe upper limbs was determined using BBT. The more-affected side ofeach child was evaluated. Correlations were assessed using Pearson’s and Spearman’s test. Results: Pronation contracture and wrist flexion deformities were the most common problems in this study. Correlations in children with cerebral palsy between the UERS and BBT (Pearson’s correlation, r = 0.5188;p<0.0001), and between UERS and MACS (Spearman’s correlation, r = -0.5217;p<0.0001) were statistically significant. Conclusion: There is a significant correlation between range of motion and functional performance of upper limbs in cerebral palsy patients. This suggests that strategies to improve in range of motion of upper limbjoints should be emphasized in order to improve the functional performance in children with cerebral palsy.